Securing Judicial Information: Assessment of Records Security in Nyahururu and Nakuru Law Courts - Oyaro, Moureen Moige; Gichohi, Paul Maku; Nzioka, Catherine (International Journal of Professional Practice, 2023)
Records play an integral role in the administration of justice and overall protection of human rights. Court records provide information, testimonies and evidence about cases presented; thereby, impacting the promptness and fairness of judgments rendered by judicial officials. Nonetheless, security breaches in handling of court records have resulted in the occurrence of missing files and inadvertent exposure of confidential information. These breaches have led to delays and significantly impacted the efficient administration of justice. This study examined the measures put in place to secure records in a bid to foster administration of justice at the Nakuru and Nyahururu law courts. The Records Continuum Model (RCM) guided the study. A descriptive survey design was utilized, targeting the 72 staff members from Nakuru and Nyahururu law courts. Due to the small population size, a census sampling technique was employed, resulting in a sample of 72 staff. Both questionnaires and interviews were used to collect data. Pretesting was done to check the validity and reliability of research tools, in tandem with expert review. Percentages and frequencies analyzed the quantitative data, while thematic analysis was used on the qualitative data. The findings revealed that law courts have implemented measures to protect court records. Nevertheless, there is room for further enhancement of measures put in place to ensure security of court records. The study concluded that there is a positive correlation between security measures and the promotion of judicial justice administration, and the need to therefore up-scale security measures. It recommends a comprehensive approach to revamp security measures at the law courts; integration of robust policies and innovation technologies in the protection of records; professional development programs for staff to enhance their competencies in handling security protocols; and regular monitoring and auditing of user access in order to detect and address unauthorized activities promptly.